(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This study aims to determine student achievement through the media of diversity books. Therefore, we use this media as a solution offered by using learning media in the Civics learning process that suits the needs of students. Therefore, the use of learning media that creates an interactive learning process can be one of the solutions to the above problems. This study uses qualitative methods which produce interesting learning outcomes. Diversity books are included in the picture book category. The use of picture books provides great benefits for children’s learning